Proposal of a Chemical Mechanism for Mini-Beam and Micro-Beam Efficacy - Dal Bello, Riccardo; Becher, Tobias; Fuss, Martina C.; Krämer, Michael; Seco, Joao (Frontiers in Physics, 2020)
This simulation study proposes a chemical mechanism to define a surrogate to the tumor control during micro- and mini-beam radiation therapy (MBRT). The main focus is proton-MBRT (pMBRT) and the methods developed are applied also to photon-MBRT (xMBRT). MBRT was reported to provide tumor control with reduced side effects when compared to standard dose delivery. The underlying mechanisms leading to a differential response of the normal tissue and the tumor are still unknown. In this work, we propose a chemical mechanism to describe the efficacy of MBRT. The model was developed starting from the observation that pMBRT led to long term survival without significant side effects of rats implanted with a high-grade glioma. We investigated whether the distribution of a generic radiation-induced molecule or radical could be a surrogate to describe the biological effect. The specific mechanisms leading to cell damage were outside the scope of this work. The molecules and radicals were selected according to a set of properties: (i) they should be stable to allow diffusion achieving coverage of the dose-valleys, (ii) they should reach a steady state in production versus removal, (iii) they should be a product of water radiolysis and (iv) they should have oxidizing capacity. A convolution model was developed to assess the property (i) keeping the analysis as general as possible. The tumor coverage was defined widening the interpretation of the ICRU-62 recommendations. The properties (ii) and (iii) were investigated with the TRAX-CHEM software. The property (iv) was used to exclude not relevant chemical species. The results show that hydrogen peroxide fulfills all the requirements. Moreover, the modelling of its temporal and spatial distributions demonstrate that a uniform coverage of the target by this reactive oxygen specie (ROS) can be achieved during the beam-on time. The model was compared and proven to be compatible with two independent photon micro-beam and proton mini-beam animal experiments. We conclude that hydrogen peroxide is a good candidate to describe the mini-beam and micro-beam efficacy. Further experiments are proposed to experimentally benchmark the model and to correlate the hydrogen peroxide concentration to the tumor control probability.